Simulations for the Discipline Specific and Professional Education of Foreign Policy Graduates - Kelton, Maryanne; Kingsmill, Verity (Journal of University Teaching and Learning Practice, 2016)
Increasingly universities aim to provide students with opportunities to graduate with skills ready to perform in the workplace. However, workplace-based opportunities for students enrolled in foreign policy subjects are more limited due to the diplomatic and sensitive political nature of the professional work. Thus there exists a need for higher education institutions teaching foreign policy courses in generalist degrees to create innovative solutions to enable student experience of professional foreign policy practice. In this article we analyse our Australian foreign policy dual strategy teaching initiative where we deploy in-person simulations enabling students to develop both their discipline specific foreign policy knowledge and gain insights in, and experience with, professional competencies and non-technical skills. Student, industry, and staff participant feedback demonstrates the benefits of the simulations for both discipline specific learning and professional skills development.